Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2006
DOI: 10.1002/dvdy.20875
|View full text |Cite
|
Sign up to set email alerts
|

Study of Pax6 mutant rat revealed the association between upper incisor formation and midface formation

Abstract: In this study, we investigated the process of supernumerary upper incisor formation in the Pax6 mutant rat, rSey 2 /rSey 2 , which exhibits a facial cleft between the medial nasal and maxillary processes. Histological investigation and epithelial labeling studies of wild type rat embryos indicated that the upper incisor develops by fusion of two primary dental placodes (PDPs) in the medial nasal process with a contribution from the epithelium of the maxillary process. In the rSey 2 /rSey 2 embryo, both PDPs ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 30 publications
0
31
1
Order By: Relevance
“…In Eda mutants, only very rare cases of side-by-side upper incisor duplication have been reported (Sofaer, 1969); we did not detect this phenotype during our observation of 60 heterozygous and 80 null Eda mutants in previous studies (Charles et al, 2009a;Charles et al, 2009b). Pax6 mutant rats, as Pax6-Sey mice, also exhibit supernumerary incisors, and it has been suggested that these incisors result from the total lack of fusion between two components of the epithelial incisor anlage separated by a cleft lip (Kriangkrai et al, 2006) and not from the secondary splitting of the incisor anlage as we have observed. Splitting of the incisor anlage might occur in nestin-cre/K5-lacZfl-smad7 mice, but the splitting seemed to be a transient event, as the two incisors were fused at their base (Klopcic et al, 2007).…”
Section: The Duplicated Incisors Belong To the Same Generation And Arcontrasting
confidence: 57%
“…In Eda mutants, only very rare cases of side-by-side upper incisor duplication have been reported (Sofaer, 1969); we did not detect this phenotype during our observation of 60 heterozygous and 80 null Eda mutants in previous studies (Charles et al, 2009a;Charles et al, 2009b). Pax6 mutant rats, as Pax6-Sey mice, also exhibit supernumerary incisors, and it has been suggested that these incisors result from the total lack of fusion between two components of the epithelial incisor anlage separated by a cleft lip (Kriangkrai et al, 2006) and not from the secondary splitting of the incisor anlage as we have observed. Splitting of the incisor anlage might occur in nestin-cre/K5-lacZfl-smad7 mice, but the splitting seemed to be a transient event, as the two incisors were fused at their base (Klopcic et al, 2007).…”
Section: The Duplicated Incisors Belong To the Same Generation And Arcontrasting
confidence: 57%
“…These previous reports suggest that activation of Wnt signaling by loss of function of its inhibitors leads to supernumerary teeth (20). Pax6, a paired homeobox protein transcription factor, is involved in neuronal and craniofacial development, including that of the optic and olfactory systems (14). In Pax6 rSey2/rSey2 mutant rats, histological analysis at E13.0 showed two dental placodes that were far apart, which was as opposed to those of wild-type embryos, and showed supernumerary incisors near the original upper incisor at E20 (14).…”
Section: Discussionmentioning
confidence: 96%
“…Pax6, a paired homeobox protein transcription factor, is involved in neuronal and craniofacial development, including that of the optic and olfactory systems (14). In Pax6 rSey2/rSey2 mutant rats, histological analysis at E13.0 showed two dental placodes that were far apart, which was as opposed to those of wild-type embryos, and showed supernumerary incisors near the original upper incisor at E20 (14). CEBPB (CCAAT/enhancer-binding protein beta)is a transcription factor that binds to consensus sequences and regulates the transcription of various genes involved in proliferation and differentiation; it is also suggested to be an important factor in osteogenesis and odontogenesis (35).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interruption in the growth and merging of midfacial processes during E11-12 in rat embryos, may lead to facial defects such as cleft lip. The cleft lip is a merging failure between the MxPs and MNPs, while the median cleft lip is a merging failure of the MNPs into midline [4, 5]. …”
Section: Introductionmentioning
confidence: 99%